Three Decades of Forest Genetics and Tree Improvement - Emmanuel, C. J. S. K.; Kapoor, M. L.; Sharma, V. K. (Indian Forester, 1992)
The paper summarizes the research work carried out on forest genetics and tree improvement of important forest tree species by Forest Research Institute, Dehra Dun and its sister organizations during the past three decades under different projects/schemes. The species taken up for genetic improvement were Tectona grandis, Bombux ceiba, Pinus spp, Dalbergia sissoo, Santalum album, Morus alba, Pterocarpus santalinus, Acacia nicotica, Acacia catechu, Eucalyptus and Albizia spp. Different methods of genetic improvement viz. selection, hybridization, induced polyploidy and induced mutageneis, were tried. This task also involved the selection of plus trees, creation of seed production areas, establishment of seed orchards, and laying of provenance trials etc. Apart from genetic improvement, work was also carried on vegetative propagation by budding, grafting, air layering including tissue culture and suitable techniques developed which have great potential for establishing clonal seed orchard, and conservation and multiplication of desired novel genotypes.The significant achievements made in these directions are detailed in this paper.